Kajian aktivitas pedagang ikan di era new normal di Pasar Wowoli Kecamatan Toari Kabupaten Kolaka - Hartati, Rani Yovi; Lawelle, Sjamsu Alam; Rosmawati; Nurdiana A; Siang, Roslindah Daeng (Universitas Halu Oleo, 2023)
This study aims to determine the activities of fish traders in the new normal era at Wowoli Market and the profits obtained by fish traders in the new normal era at Wowoli Market, Toari District, Kolaka Regency. This research was conducted in December 2021 during the Covid-19 pandemic. Determination of the sample in this study using the census method amounted to 15 fish traders. This study uses data collection methods, namely through literature study, observation, interviews, and documentation. The data analysis used is descriptive qualitative analysis and profit analysis. The result showed that the activities of fish traders in the normal era at Wowoli Market, Toari Districk, Kolaka Regency included preparation before tranding, activities while at the market, and after tranding the same as activities in the normal era. Overall activities of fish traders in the new normal er were carried out by implementing health protocols. Like wering a mask. When the new normal, traders activities are starting to recover where the implementation of health protocols is no longer significantly implemented, such as washing hands in running water using gloves using a hand sanitaizer, checking body temperature and keeping a safe distance. The average profit level of tranding profits in the normal er ad the normal era is different. In the normal era profits Rp1.342.999/month. These profits are influenced by an increase in the number of visits by community buyers, while in the normal era, profits for fish traders amounted to Rp1.159.999/month with factors affecting the reduction in community visit due to the Covid-19 pandemic.